2016
DOI: 10.1111/pcmr.12469
|View full text |Cite
|
Sign up to set email alerts
|

Roles of reactive oxygen species in UVA‐induced oxidation of 5,6‐dihydroxyindole‐2‐carboxylic acid‐melanin as studied by differential spectrophotometric method

Abstract: Eumelanin photoprotects pigmented tissues from ultraviolet (UV) damage. However, UVA-induced tanning seems to result from the photooxidation of preexisting melanin and does not contribute to photoprotection. We investigated the mechanism of UVA-induced degradation of 5,6-dihydroxyindole-2-carboxylic acid (DHICA)-melanin taking advantage of its solubility in a neutral buffer and using a differential spectrophotometric method to detect subtle changes in its structure. Our methodology is suitable for examining th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 72 publications
(106 reference statements)
8
49
0
Order By: Relevance
“…Thus, it appears that during immediate pigment darkening an overall increase in visible absorption (with a decrease in UVA absorption) leads to a darkening of preexisting eumelanin without any change in its amount. In fact, our recent study using differential spectra of a UVA‐exposed DHICA‐melanin solution vs an unexposed solution confirms the above‐mentioned spectral changes, which involves superoxide anion production . Earlier studies of the interaction of synthetic DOPA‐melanin with oxidizing and reducing radicals generated by pulse radiolysis demonstrated that while the oxidation of melanin was accompanied by a distinct increase in its absorption in the visible region, the reduction of melanin led to its decreased absorption .…”
Section: Photodegradation Of Eumelanin and Pheomelaninsupporting
confidence: 70%
See 3 more Smart Citations
“…Thus, it appears that during immediate pigment darkening an overall increase in visible absorption (with a decrease in UVA absorption) leads to a darkening of preexisting eumelanin without any change in its amount. In fact, our recent study using differential spectra of a UVA‐exposed DHICA‐melanin solution vs an unexposed solution confirms the above‐mentioned spectral changes, which involves superoxide anion production . Earlier studies of the interaction of synthetic DOPA‐melanin with oxidizing and reducing radicals generated by pulse radiolysis demonstrated that while the oxidation of melanin was accompanied by a distinct increase in its absorption in the visible region, the reduction of melanin led to its decreased absorption .…”
Section: Photodegradation Of Eumelanin and Pheomelaninsupporting
confidence: 70%
“…This reaction was confirmed with a synthetic DHICA‐melanin solution . Our latest study showed that singlet oxygen is generated and quenched during the UVA‐induced oxidation of DHICA‐melanin, which likely leads to cleavage of the indolequinone moiety to form free PTCA. Singlet oxygen is a highly reactive molecule that reacts with a variety of biomolecules, including aromatic amino acids and nucleotides.…”
Section: Photodegradation Of Eumelanin and Pheomelaninsupporting
confidence: 55%
See 2 more Smart Citations
“…Pyrrole derivatives identified as markers of eumelanin crosslinking were found in blue light‐exposed bovine RPE melanosomes and in human RPE cells, suggesting age‐related oxidative modifications to RPE melanin. Additionally, it has been shown that the UV‐A‐induced oxidation product of 5,6‐dihydroxyindole‐2‐carboxylic acid (DHICA), indole‐5,6‐quinone‐2‐carboxylic acid, can react with ROS to form endoperoxide and other reactive intermediates . It was found that cleavage of indole‐5,6‐quinone‐2‐carboxylic acid ultimately leads to the formation of pyrrolic moieties previously implicated as markers of melanin degradation.…”
Section: Discussionmentioning
confidence: 99%